Little things that mean a lot in managing beef cattle - Pretzer, D. (Kansas State University. Agricultural Experiment Station, 2011)
Survival in the beef cattle business for the next year or so will depend on doing little things well, says Don Pretzer, extension farm management specialist at Kansas State. "Doing enough little things right will add up to big differences in profitability. no matter whether you're a cow-calf operator, a backgrounder or a cattle finisher.” He offers some interesting ideas for cattle ranchers. The economist says cow herd costs are running around $375 per cow-calf unit per year. This includes $178 for feed, including pasture for 15% replacements. 15% interest on the value of the cow ($450) and $32 a year for 1abor. "A 92% calf crop with steer sale weights averaging 475 lbs. and heifers at 425 lbs. indicates the producer needs $98 cwt. for his steers and $92 cwt. for heifers to cover all of his costs." the economist notes. Current prices of $67 and $61. respectively, show a full-cost loss of $101 per cow-cal f unit.” The specialist says survival strategy warrants looking only at cash costs, including rented grass. On a cash cost budget, the breakevens are at $70 and $64 cwt ., resulting in a $9-per-unit loss per year.
Keywords: Beef; Income; Calf crop; Grain